Institutional Capacity Building Through Learning Organisation Principles: A Case Study of The Health Training Centre in Riau - Herman Efendi; Kiswanto; Yessi Harnani; Dedi Widodo; Syafrani (Viva Medika, 2024)
The Riau Provincial Health Service Health Training Center UPT Institute has an important role in improving the Training Institute using the Learning Organization method. This research uses the Watkins & Marsick Approach model which includes seven dimensions of Learning Organization. At the individual level there are two dimensions, namely Continuous Learning and Inquiry and Dialogue. At the team/group level it is reflected in Team Learning. At the organizational level there are four dimensions, namely Embedded System, Empowerment, System Connection, and Strategic Leadership.  There were 8 informants. Triagulation is used in sources, methods and data. The research results show that the three dimensions of the Learning Organization have been running, with several obstacles. The other four dimensions, namely Organizational Culture, Embedded System, Empowerment, and System Connection are still not optimal. The main obstacles include ineffective communication, low motivation, limited understanding of technology, and lack of infrastructure support. Strategic Leadership alsoneeds to be improved to provide better guidance and resources. This research highlights the importance of improving communication, motivation, and understanding of technology to achieve better organizational performance. Apart from that, the implementation of the Embedded System, Empowerment, System Connection, and Strategic Leadership also still requires improvement.  Overall, this research concludes that the UPT Health Training Center has the potential to become a more effective Learning Organization, requiring more comprehensive efforts in increasing human resource capacity, building an organizational culture that supports learning, and aligning leadership strategies with Learning Organization principles. Recommendations for UPT Bapelkes Riau Province to strengthen continuous learning, inclusive dialogue, team learning, and technology-based systems for efficiency.